THE EFFECT OF MODIFIED RAMPED POSITION ON OXYGEN SATURATION IN OBESE PATIENTS UNDER GENERAL ANESTHESIA - Ety Azhara Laila Najmi; Niken Anggraini Sri Saputri; Vita Purnamasari (Journal of Indonesian Anesthesiology Nursing, 2026)
Background: Obese patients undergoing general anesthesia are at risk of decreased oxygen saturation due to physiological changes in the respiratory system and the effects of anesthetic agents. Patient positioning during ventilation is an important factor in maintaining oxygenation, one of which is the modified ramped position that can improve pulmonary ventilation and perfusion. Methods: This quantitative study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 35 respondents selected using a consecutive sampling technique. Data were collected using observation sheets and oxygen saturation (SpO₂) measurements with a pulse oximeter before and after the intervention. Data analysis was performed using the Wilcoxon Signed-Rank Test. Results: There was a significant effect of the modified ramped position on changes in oxygen saturation (p = 0.000 ≤ 0.05). Before the intervention, 96.7% of respondents experienced low oxygen saturation (<95%). After the intervention, 90% of respondents achieved normal oxygen saturation in the first minute, and all respondents (100%) achieved normal saturation by the second and third minutes. Conclusion: The modified ramped position was effective in improving oxygen saturation in obese patients under general anesthesia.